Partisipasi Masyarakat Dalam Pembangunan: Studi Kasus Di Kelurahan Utama Kecamatan Cimahi Selatan – Kota Cimahi Jawa Barat - Iriani, Enni (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2011)
appropriate step to improve the condition of Indonesia, which in 2003 declared the sixth poorest country in the world. Meanwhile, World Bank states that the empowerment and community participation is a strategic step to address the problem of poverty, economic, social and cultural rights. In line with that, the Indonesian government issued Law No. 22 of 1999 on Regional Governance and Law No. 25 of 1999 concerning the Central and Regional Financial Balance which explicitly states that public participation is premised governance and local development of a democratic, transparent and accountable and to realize this, the Minister of Interior issued Circular Letter No. 050/987/SJ/2003 about guidelines for the implementation of participatory development coordination forum. With that background, this research is carried out to identify shapes and mechanisms of as well as efforts to increase public participation in Kelurahan Utama Kecamatan Cimahi Selatan. One of the results of this research indicates that people understanding of community participation is still limited to the participation of all communities in any development activities, both proclaimed by the Central Government and specified in the deliberations of development